Analysis of the Impact on Compensation Satisfaction, Overcommitment, and Sleep Quality as Mediating Factor Against Mental Health Condition of Construction Worker in Indonesia - Agasi, Wenny Adelia; Nugrahedi, Dominggus Petra; Librawan, Reza Tirsadi; Prasetyaningtyas, Sekar Wulan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study investigates the relationship between compensation satisfaction, overcommitment, and sleep quality as mediating variable on the mental health of construction workers in Indonesia. The research utilizes a quantitative approach with data collected from 182 respondents through surveys conducted using a cross-sectional method. The questionnaire utilized Likert scales to measure compensation satisfaction, overcommitment, sleep quality, and mental health. The collected data were analyzed using SPSS software for descriptive analysis and multiple linear regression. The findings reveal that compensation satisfaction positively impacts mental health, while overcommitment has a negative effect, contributing to mental health deterioration. Additionally, sleep quality is found to play a mediating role, mitigating the adverse effects of overcommitment on mental health. The study highlights the significance of fair compensation and work-life balance in improving the mental health of construction workers. These insights are essential for developing management policies aimed at enhancing employee well-being in the construction sector. The research contributes to understanding the complex interplay between compensation, work stress, and mental